UMPSA Vice-Chancellor pays tribute to farmers of Kampung Bentan, Pekan - Siti Nur Azwin, Zulkapri (UMPSA, 2024)
PEKAN, 4 September 2024 – The Vice-Chancellor of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Professor Ts. Dato' Dr. Yuserrie Zainuddin, recently led a Gotong-Royong Agriculture Project with the farmers of Kampung Bentan, Pekan.